Optimal Design and Development of a Decoupled A/B-Axis Tool Head with Parallel Kinematics. (3rd January 2010) - Xie, Fugui; Liu, Xin-Jun; Wang, Li-Ping; Wang, Jinsong
Abstract : This paper is an attempt to design a decoupled A/B-axis tool head with parallel kinematics, due to the increasing demand for A/B-axis tool heads in industry, particularly in thin wall machining applications for structural aluminium aerospace components. In order to carry out further analysis, the method of orientation description based on the azimuth and tilt angles is introduced, which is a convenient method describing kinematics, parasitic motions, and orientation workspace. For the purpose of optimal design, three indices are defined to evaluate the force transmission performance of the tool head. They have obvious physical significance and are dependent of any coordinate system. Based on the indices and their performance atlases, the optimization process is presented in detail. The parasitic motions and orientation capability of the designed tool head are analyzed finally. The results show that the designed device is far from singularity, has good force transmissibility, and has very high tilting angle. The indices and analysis and design method used here should be said to be extended to other parallel robots.